STRATEGI PUBLIK RELATION DALAM PEMASARAN OBJEK WISATA WATER BOOM DI KABUPATEN POLEWALI MANDAR - muhammad Rizal; muhammad Syaeba; Hamdan Hamdan (Journal Peqguruang: Conference Series, 2024)
The purpose of this study was to determine the public relations strategy in marketing waterboom attractions in Polewali Mandar Regency. The research uses a qualitative approach to explain phenomena through deep data collection. The results show that many visitors know Polman Waterboom Tourism from social media including information on all tourist objects and what activities are carried out. In building the company's image, one of the strategies prepared by Polman Waterboom Tourism is to build attractiveness and make nature tourism much more modern and change the mindset of visitors that nature tourism is boring. Technologically, nature tourism now has many rides for games for children to adults. Even so, there is still a lack of increase in the number of visitors at the water boom rides because many new tourist objects have emerged.